Rapidly fatal necrotising fasciitis caused by Streptococcus pyogenes. Issue 7 (July 1993) - Donaldson, P M; Naylor, B; Lowe, J W; Gouldesbrough, D R
Abstract : AIMS--To describe the morbid anatomical and bacteriological features in a series of five cases of rapidly fatal Streptococcus pyogenes necrotising fasciitis. METHODS--Post mortem and bacteriological examinations were made of five patients dying within 48 hours from rapidly fatal necrotising fasciitis. RESULTS--All five cases died rapidly from a toxic Streptococcus toxin syndrome as a result of developing necrotising fasciitis following trivial injury. CONCLUSIONS--Necrotising fasciitis caused by Streptococcus pyogenes infection can be rapidly fatal. This is probably the result of a toxic shock syndrome. Rapid, early diagnosis and swift and probably empirical treatment is required to avoid a fatal outcome.